Legal Status of Recognition of Children Out of Marriage according to Article 280 KUHPerdata - Febi Ilham Fitra; Dwi Putra Jaya; Hurairah Hurairah; Ana Tasia Pase (JURNAL HUKUM SEHASEN, 2022)
Child acknowledgment in a formal sense is a form of giving information from a man who declares acknowledgment of his children. Meanwhile, in a material sense, child recognition is a legal act to create a family relationship between the child and the person who admits it. Based on Article 280 of the Civil Code, which says; that with a confession made to a child out of wedlock, a civil relationship arises between the child and his father or mother. This means that there is no legal relationship between the illegitimate child and the "father" (biologically) or "mother" in principle. The legal relationship only exists if the "father" and or "mother" give an acknowledgment that the child is his child. The purpose of this study is to find out how the legal status of children out of wedlock and the requirements for child recognition are in accordance with the Civil Code. The research method that the author uses is normative research. This research is sourced from the Civil Code regarding the recognition of children out of wedlock and based on books, articles and journals related to the research. The results of this study indicate that the legal status of child recognition out of wedlock is regulated by the Child Recognition Institution in Article 272 of the Civil Code which states that "children out of wedlock (nuturlijk kind), except those born from adultery or blasphemy of blood, each every child born”, the relationship of the child out of wedlock with his father will only exist after the father makes a confession or the child outside of marriage is recognized by the father.